Different Effects of Pre-transplantation Measurable Residual Disease on Outcomes According to Transplant Modality in Patients With Philadelphia Chromosome Positive ALL - Li, Si-Qi; Fan, Qiao-Zhen; Xu, Lan-Ping; Wang, Yu; Zhang, Xiao-Hui; Chen, Huan; Chen, Yu-Hong; Wang, Feng-Rong; Han, Wei; Sun, Yu-Qian; Yan, Chen-Hua; Tang, Fei-Fei; et al. (Frontiers in Oncology, 2020)
Background: This study compared the effects of pretransplantation measurable residual disease (pre-MRD) on outcomes in Philadelphia chromosome (Ph)-positive ALL patients who underwent human leukocyte antigen-matched sibling donor transplantation (MSDT) or who received unmanipulated haploidentical SCT (haplo-SCT). Methods: A retrospective study (n=202) was performed. MRD was detected by real-time quantitative PCR. Results: In the total patient group, patients with positive pre-MRD had a higher 4-year cumulative incidence of relapse (CIR) than that in patients with negative pre-MRD (26.1% vs. 12.1%, P=0.009); however, the cumulative incidence of nonrelapse mortality (NRM) (7.4% vs. 15.9%, P=0.148), probability of leukemia-free survival (LFS) (66.3% vs. 71.4%, P=0.480), and overall survival (OS) (68.8% vs. 76.5%, P=0.322) were comparable. In the MSDT group, patients with positive pre-MRD had increased 4-year CIR (56.4% vs. 13.8%, P<0.001) and decreased 4-year LFS (35.9% vs. 71.0%, P=0.024) and OS (35.9% vs. 77.6%, P=0.011) compared with those with negative pre-MRD. In haplo-SCT settings, the 4-year CIR (14.8% vs. 10.7%, P=0.297), NRM (7.3% vs. 16.3%, P=0.187) and the 4-year probability of OS (77.7% vs. 72.3%, P=0.804) and LFS (80.5% vs. 75.7%, P=0.660) were comparable between pre-MRD positive and negative groups. In subgroup patients with positive pre-MRD, haplo-SCT had a lower 4-year CIR (14.8% vs. 56.4%, P=0.021) and a higher 4-year LFS (77.7% vs. 35.9%, P=0.036) and OS (80.5% vs. 35.9%, P=0.027) than those of MSDT. Multivariate analysis showed that haplo-SCT was associated with lower CIR (HR, 0.288; P=0.031), superior LFS (HR, 0.283; P=0.019) and OS (HR, 0.252; P=0.013) in cases with a positive pre-MRD subgroup. Conclusions: Our results indicate that the effects of positive pre-MRD on the outcomes of patients with Ph-positive ALL are different according to transplant modality. For Ph-positive cases with positive pre-MRD, haplo-SCT might have strong graft-versus-leukemia (GVL) effects.